Sistem Pakar Diagnosa Penyakit Kulit Akibat Gigitan Serangga Menggunakan Teorema Bayes - Bagas Irvan Bagaskara; Agus Sidiq Purnomo (Universitas Mercu Buana Yogyakarta, 2021)
This research was to design an expert system to diagnose skin diseases caused by insect bites using Bayes’ Theorem. Bayes' Theorem is a theorem used in statistics to calculate the probability of a hypothesis. The basis of the expert system knowledge is derived from the acquisition of doctors’ knowledge. This study used 25 data of medical records. The medical records were implemented into the system. The results of the system were matched with the experts to get the maximum matching number and a close identification result. Based on the 25 patient data tested against the experts and the system, the system could detect 4 types of skin diseases caused by insect bites, namely Scabies, Insect Bite, Atopic Dermatitis, and Prurigo Simplex. Of the 25 patients who had skin diseases caused by insect bites and had been matched with the experts’ validation, 21 of them matched and 4 did not match. The accuracy level of the system based on the results of the experts’ validation and the system was 84%.